2017
DOI: 10.1186/s13063-017-1823-9
|View full text |Cite
|
Sign up to set email alerts
|

Unravelling effectiveness of a nurse-led behaviour change intervention to enhance physical activity in patients at risk for cardiovascular disease in primary care: study protocol for a cluster randomised controlled trial

Abstract: BackgroundSelf-management interventions are considered effective in patients with chronic disease, but trials have shown inconsistent results, and it is unknown which patients benefit most. Adequate self-management requires behaviour change in both patients and health care providers. Therefore, the Activate intervention was developed with a focus on behaviour change in both patients and nurses. The intervention aims for change in a single self-management behaviour, namely physical activity, in primary care pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
30
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(30 citation statements)
references
References 61 publications
0
30
0
Order By: Relevance
“…Accordingly, parallel to the evaluation of the effectiveness of a behaviour change intervention (the Activate intervention) in a cluster-randomised controlled trial comparing the Activate intervention to care as usual, we planned to evaluate the intervention delity. The Activate intervention is a nurse-led behaviour change intervention to enhance physical activity in primary care patients at risk for cardiovascular disease (CVD) [11]. In the trial, 195 patients of 31 general practices throughout the Netherlands participated.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Accordingly, parallel to the evaluation of the effectiveness of a behaviour change intervention (the Activate intervention) in a cluster-randomised controlled trial comparing the Activate intervention to care as usual, we planned to evaluate the intervention delity. The Activate intervention is a nurse-led behaviour change intervention to enhance physical activity in primary care patients at risk for cardiovascular disease (CVD) [11]. In the trial, 195 patients of 31 general practices throughout the Netherlands participated.…”
Section: Introductionmentioning
confidence: 99%
“…Prior conducted process evaluation covered the delity dimensions study and intervention design, provider training, treatment receipt and enactment of treatment skills [11,13,14]. The evaluation of the intervention design showed that the use of the Behaviour Change Wheel [15], as theoretical framework for developing the Activate intervention and use of a cluster-RCT design allowed for addressing the research questions [11].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Behaviour change is a sustained process, which, if it is to be successfully initiated, necessitates a positive relationship between the provider (counsellor or practitioner) and the client (patient), built on trust and effective communication . Patients trust and appreciate the significance of prescription forms issued to them by their consulting clinician .…”
Section: Introductionmentioning
confidence: 99%